Preparation method of ionic liquid modified nanogold cluster material and application of ionic liquid modified nanogold cluster material in detection of heavy metal ion cadmium

By designing nano-gold cluster composites modified with ionic liquids as fluorescent probes, the rapid, economical and sensitive problems of cadmium ion detection in the prior art are solved, and high sensitivity and specific detection of cadmium ions are achieved, with broad food safety monitoring application prospects.

CN119505868AActive Publication Date: 2025-02-25SOUTH CENTRAL UNIVERSITY FOR NATIONALITIES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411636744.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The prior art is difficult to detect cadmium ions quickly, economically and sensitively, especially in complex substrates, which have problems such as complex operation, expensive equipment and long analysis time.

Method used

A composite material of nano-gold clusters modified by ionic liquid was designed, and nano-gold clusters synthesized by imidazole ionic liquid and bovine serum albumin were modified by electrostatic interaction to form [C16M2Im]Br@BSA- Au NCs composite material, used as fluorescent probe for detection of cadmium ions.

Benefits of technology

Fast, sensitive and specific detection of cadmium ions is achieved, with the detection limit reaching 5.09×10-9M, far lower than the limit specified by the World Health Organization and the International Organization for Standardization, and can accurately identify cadmium ions in complex substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005137315030000022
    Figure BDA0005137315030000022
  • Figure FDA0005137315020000011
    Figure FDA0005137315020000011
  • Figure FDA0005137315020000012
    Figure FDA0005137315020000012
Patent Text Reader

Abstract

The invention belongs to the technical field of heavy metal ion detection, and particularly discloses a preparation method of an ionic liquid modified nanogold cluster material and application of the ionic liquid modified nanogold cluster material in detection of heavy metal ion cadmium. According to the invention, bovine serum albumin is taken as a stabilizing agent and a reducing agent, a nanogold cluster emitting red fluorescence is synthesized, and the ionic liquid modified nanogold cluster composite material is synthesized by utilizing electrostatic interaction between imidazolium ionic liquid and BSA (Bovine Serum Albumin). Due to the unique coordination effect between the cadmium ions and the imidazolium ionic liquid, the cadmium ions can effectively enhance the fluorescence intensity of the ionic liquid modified nanogold cluster composite material, the ionic liquid modified nanogold cluster composite material can be applied to detection of the cadmium ions in an actual sample, and a new thought is provided for convenient detection of the cadmium ions in a complex matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heavy metal ion detection, and particularly relates to a preparation method of an ionic liquid modified nano-gold cluster material and an application thereof in the detection of heavy metal ion cadmium. Background Art

[0002] Heavy metals are widely used in industry and agriculture. However, heavy metal ion pollution also poses a serious threat to human health and ecosystems. Among various heavy metal ions, cadmium is one of the most toxic and harmful heavy metals, and is widely used in nickel-cadmium batteries, plastic colorants, cigarettes, etc. Unlike many other heavy metals, cadmium does not participate in biological processes and is not an essential element for the human body. Therefore, even at extremely low concentrations, cadmium can have adverse effects on organisms through bioaccumulation. Cadmium easily accumulates in human organs, causing damage to organs such as the kidneys and liver. Long-term exposure to cadmium can damage blood vessels and systems, and even increase the risk of cancer. Therefore, the establishment of a sensitive Cd 2+ Quantitative detection methods are crucial. 2+ The determination of Cd is mostly carried out by traditional methods such as atomic absorption spectroscopy (AAS), atomic emission spectroscopy (AES), and inductively coupled plasma mass spectrometry (ICP-MS). However, these methods cannot meet the requirements of rapid detection of Cd due to the professional operation, expensive instruments, and long analysis time. 2+ Therefore, it is necessary to establish an economical, convenient and sensitive Cd 2+ Detection methods are of great significance to environmental protection and human health.

[0003] Fluorescence spectroscopy has the advantages of high sensitivity, ease of use, and high cost-effectiveness. Fluorescent probes are used for specific analytes, including metal ions, inorganic anions, and biologically important small molecules. It has attracted great interest due to the high sensitivity, convenience, and rapid response of optical detection methods. However, due to the high concentration of other heavy metal ions such as Zn in food and the environment, the 2+ The high abundance of Cd 2+ Sensors require strict metal ion specificity. As a green and environmentally friendly functional material, ionic liquids have the advantages of highly controllable structure, negligible vapor pressure, good thermal stability, etc. They can act as functional modifiers and good solvents. In particular, based on the designability of ionic liquids, the properties of materials such as nanogold and quantum dots can be regulated. The resulting composite materials have great potential in the field of analytical detection, such as pesticide, metal ion, antibiotic detection, etc. Summary of the invention

[0004] The object of the present invention is to design and synthesize a method for detecting cadmium ions as a fluorescent probe using a nano-gold cluster composite material modified by an ionic liquid for the purpose of addressing the deficiencies in the prior art. The method utilizes the electrostatic interaction between an imidazole ionic liquid and BSA to synthesize a nano-gold cluster composite material modified by an ionic liquid, thereby achieving specific detection of cadmium ions in food. Due to the unique coordination between cadmium ions and imidazole ionic liquids, cadmium ions can effectively enhance the fluorescence intensity of the nano-gold cluster composite material modified by the ionic liquid, and can be used to detect cadmium ions in actual samples. The probe designed and synthesized by the method has the advantages of high sensitivity and good specificity, can be applied to the detection of cadmium ions in actual samples, and provides a new idea for the convenient detection of cadmium ions in complex matrices.

[0005] The present invention uses bovine serum albumin (BSA) as a stabilizer and a reducing agent to synthesize red fluorescent nanogold clusters, and 16 M 2 Im]Br ionic liquid was mixed with BSA-Au NCs by simple stirring, [C 16 M 2 Im]Br ionic liquid can interact electrostatically with BSA on the surface of BSA-Au NCs, thereby modifying the surface of BSA-AuNCs. 16 M 2 Im]Br@BSA-Au NCs composites were used as fluorescent probes for rapid and sensitive quantitative detection of cadmium ions. The detection limit was 5.09×10 -9 M, which is far below the limit of 0.5 mg / L (food) stipulated by the World Health Organization (WHO) and the International Organization for Standardization (ISO). In view of the interference of other heavy metal ions in complex matrices, the probe showed selective specificity for cadmium ions among 15 heavy metal ions and 12 other interfering ions. At the same time, the constructed sensor can also be used for the detection of cadmium ions in a variety of actual samples.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] The invention discloses a method for detecting cadmium ions by using an ionic liquid modified nano-gold cluster composite material as a fluorescent probe. The ionic liquid modified nano-gold cluster composite material and a sample solution to be tested are mixed and reacted for a certain time (preferably, the mixture reacts for 5±0.5 min), and the fluorescence emission spectrum of the probe is measured. If the fluorescence intensity at 620±5 nm increases after the sample solution to be tested is added, it is determined that the sample solution to be tested contains cadmium ions; otherwise, the sample solution to be tested does not contain cadmium ions.

[0008] The imidazole ionic liquid is mixed with the nano-gold clusters synthesized by taking bovine serum albumin as a stabilizer and a reducing agent to obtain the nano-gold cluster composite material modified by the ionic liquid.

[0009] The preparation method of the ionic liquid modified nano-gold cluster composite material comprises: (1) treating HAuCl 4 The solution is mixed with a bovine serum albumin solution, the pH range is adjusted to 11-12, and the mixture is stirred vigorously to synthesize a red fluorescent nano-gold cluster solution; (2) the imidazole ionic liquid solution is mixed with the nano-gold cluster solution, and the mixture is stirred to allow electrostatic interaction between the two to produce an ionic liquid-modified nano-gold cluster composite material.

[0010] In step (1), the HAuCl 4 The dosage ratio of HAuCl to bovine serum albumin is 1 mmol:5 g. 4 The volume ratio of the HAuCl solution to the bovine serum albumin solution is 1:1. More preferably, the HAuCl 4 The concentration of the solution was 10 mM.

[0011] In step (1), NaOH solution is added to adjust the pH range, and the concentration of the NaOH solution is 1.0 M.

[0012] In step (1), the stirring time is 24 h and the stirring temperature is 37 °C.

[0013] In step (2), the molar ratio of the imidazole ionic liquid to the nanogold is 2: 1. Preferably, the volume ratio of the imidazole ionic liquid solution to the nanogold cluster solution is 1: 1. More preferably, the concentration of the imidazole ionic liquid solution is 10 mM.

[0014] The structural formula of the imidazole ionic liquid is as follows:

[0015] R is an alkyl group having 12 to 16 carbon atoms, preferably a straight-chain alkyl group having 12 to 16 carbon atoms; X is Br, Cl or I.

[0016] Preferably, the chemical formula of the imidazole ionic liquid is [C 16 M 2 Im]Br, its structural formula is as follows:

[0017]

[0018] The detection limit of the ionic liquid modified gold nanocluster composite material as a fluorescent probe is 5.09×10 -9 M.

[0019] In step (2), the stirring time is 30 min.

[0020] Furthermore, a method for detecting cadmium ions using an ionic liquid-modified nanogold cluster composite material as a fluorescent probe comprises the following steps: S1 drawing a standard fitting curve of cadmium ions: mixing the ionic liquid-modified nanogold cluster composite material and a series of cadmium ion solutions with different concentrations, fixing the volume, and measuring the fluorescence emission spectrum of the probe after oscillation (for example, a rotation speed of 300-400 r / min) or standing for 5 minutes, using the fluorescence intensity difference of 620±5nm before and after adding cadmium ions as the ordinate and the cadmium ion concentration as the abscissa for linear calibration to obtain a standard fitting curve for fluorescence detection;

[0021] S2 mixes the ionic liquid modified nanogold cluster composite material and the sample solution to be tested, fixes the volume, shakes (for example, at a rotation speed of 300-400 r / min) or allows to stand for 5 minutes, then measures the fluorescence emission spectrum of the probe, and calculates the cadmium ion concentration in the sample solution to be tested using the fitting curve in S1.

[0022] The cadmium ion concentration in the sample solution to be tested is 1.0×10 -8 –1.0×10 -6 M.

[0023] The sample to be tested is food, including beverages and grains, and the raw material or dilution thereof or the extract obtained by simple pretreatment has a cadmium ion concentration of 1.0×10 -8 –1.0×10 -6 M.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention successfully synthesized a functionalized ionic liquid modified [C 16 M 2 Im]Br@BSA-Au NCs composites and applied them to the rapid and accurate quantitative detection of cadmium ions. When cadmium ions were added, [C 16 M 2 The red fluorescence of Im]Br@BSA-Au NCs composite material has a significant fluorescence enhancement effect. 16 M 2 The linear range of fluorescence method for cadmium ions of Im]Br@BSA-Au NCs composites is 1.0×10 -8 –1.0×10 -6 M, the detection limit can reach 5.09×10 -9M. In addition, the designed and synthesized probe can selectively identify cadmium ions from 15 heavy metals and 12 other interfering ions (100 times higher than the concentration of cadmium ions), with good specificity. After simple pretreatment of actual samples, the probe can achieve quantitative detection of cadmium ions, providing a new idea for sensitive and rapid detection of cadmium ions in complex matrices.

[0026] The present invention provides a sensitive fluorescence platform for the determination of cadmium ions in food, which has high accuracy, high sensitivity, good linear range, avoids the defects of large equipment and long time consumption compared with the existing detection methods, and has no high professional requirements for operators. 2+ The detection provides a new method and has broad application prospects in food safety monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 In this invention, BSA-Au NCs and [C 16 M 2 Im]Br@BSA-AuNCs composites with fluorescence intensity as the ordinate and wavelength as the abscissa (inset a and b are BSA-Au NCs and [C 16 M 2 (Figure 5) Fluorescence color diagram of Im]Br@BSA-Au NCs composite material at 365 nm.

[0028] Figure 2 For the present invention, [C 16 M 2 In the composite material of Im]Br@BSA-AuNCs, the addition of [C 16 M 2 Optimization diagram of the concentration of Im]Br, before and after adding cadmium ions [C 16 M 2 The fluorescence enhancement intensity (F 1 -F 0 ) is the ordinate, with [C 16 M 2 The concentration of Im]Br is on the horizontal axis.

[0029] Figure 3 The BSA-Au NCs and [C 16 M 2 Transmission electron microscopy images of Im]Br@BSA-AuNCs composites, where a is the TEM image of BSA-Au NCs and b is the TEM image of [C 16 M 2 TEM image of Im]Br@BSA-AuNCs composite material.

[0030] Figure 4 The present invention is based on [C 16 M 2 The fluorescence enhancement intensity (F 1 -F 0 ) as the ordinate and cadmium ion concentration (10-1000nM) as the abscissa.

[0031] Figure 5 The present invention is based on [C 16 M 2 Im]Br@BSA-AuNCs composites were added with Cd 2+ A bar graph with the fluorescence intensity after different interfering ions as the ordinate and the type of heavy metals as the abscissa.

[0032] Figure 6 The present invention is based on Cd 2+ After adding different interfering ions in the presence of 16 M 2 A bar graph with the fluorescence intensity of the Im]Br@BSA-AuNCs composite material as the ordinate and the types of interfering ions as the abscissa.

[0033] Figure 7 The spiked recovery results of the present invention in actual samples (rice, sea buckthorn juice, roxburgh juice, West Lake Longjing, Pu'er tea, white wine, yellow wine, apple juice, grape juice and packaged drinking water) are shown. DETAILED DESCRIPTION

[0034] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific examples, but the content of the present invention is not limited to the following examples, and the following content should not be understood as limiting the scope of protection of the present invention.

[0035] The chemical reagents and solvents used in the examples were of analytical grade.

[0036] In the following examples, the fluorescence spectrum measurement conditions are all as follows: the emission wavelength is 500-700 nm, the excitation wavelength is 365 nm, and the slit width is 10 nm.

[0037] Example 1

[0038] A [C 16 M 2 The synthesis of Im]Br@BSA-Au NCs composite material, the specific synthesis method is as follows:

[0039] (1) Synthesis of BSA-AuNCs:

[0040] Prepare 50 mg / mL BSA and 10 mM HAuCl in double distilled water. 4 In a 50 mL round-bottom flask in a 37°C water bath, stir continuously 15 mL of HAuCl 4 The solution was added to 15 mL of BSA solution. After 2 min, 1.5 mL of 1.0 M NaOH solution was added, the pH was adjusted to 12, and the mixture was vigorously stirred at 37 ° C for 24 h. The color of the mixture gradually changed from light yellow to brownish yellow, indicating that the synthesis of BSA-Au NCs was successful (concentration was about 5 mM).

[0041] (2)[C 16 M 2 Synthesis of Im]Br@BSA-Au NCs composites:

[0042] 15 mL of different concentrations (5 mM, 8 mM, 9 mM, 10 mM, 12 mM, 15 mM, 20 mM) of [C 16 M 2 Im]Br solution (prepared with double distilled water) and 15 mL of 5 mM BSA-AuNCs solution synthesized in step (1) were mixed in a 50 mL round-bottom flask and gently stirred for 30 min at room temperature to obtain a series of [C 16 M 2 Im]Br@BSA-Au NCs composites.

[0043] First, a 100 μL series of [C 16 M 2 Im]Br@BSA-Au NCs composites were mixed with 900 μL of deionized water and the series [C 16 M 2 The original fluorescence intensity of Im]Br@BSA-Au NCs composites was obtained. 0 Then, 100 μL of [C 16 M 2 Im]Br@BSA-Au NCs composites were added to a centrifuge tube with 100 μL of 1 μM cadmium chloride solution, and then the volume was adjusted to 1.0 mL with deionized water. After shaking (25 °C, 350 r / min) for 5 min, a series of [C 16 M 2 The fluorescence emission spectrum of the Im]Br@BSA-AuNCs composite probe was obtained. 1 ; before and after adding cadmium ions [C 16 M 2 The fluorescence enhancement intensity (F 1 -F 0 ) is the ordinate, with [C16 M 2 The concentration of Im]Br is used as the horizontal axis to obtain the concentration optimization diagram. Figure 2 As shown, when adding [C 16 M 2 When the concentration of Im]Br solution is 10mM, [C 16 M 2 Im]Br@BSA-Au NCs composites and Cd 2+ The fluorescence enhancement effect before and after the reaction is the best, so [C 16 M 2 The specific concentration of 1 m]Br was 10 mM.

[0044] 10 mM [C 16 M 2 The materials before and after Im]Br modification were tested by fluorescence spectroscopy, such as Figure 1 As shown, [C 16 M 2 The fluorescence intensity of the Im]Br@BSA-Au NCs composite material was higher than that of pure BSA-Au NCs, and both of them emitted bright red fluorescence. 16 M 2 Im]Br@BSA-Au NCs and BSA-AuNCs materials were characterized by transmission electron microscopy, such as Figure 3 As shown in Figure 2, the particle size of BSA-Au NCs is about 2-3 nm (the scale bar in the lower right corner is 50 nm), and after modification [C 16 M 2 The particle size of the Im]Br@BSA-Au NCs composite material is approximately 50-200nm (the scale bar in the lower right corner is 2.0um). The results show that the particle size of the modified composite material is significantly increased.

[0045] Example 2

[0046] [C 16 M 2 Im]Br@BSA-Au NCs composite material was used as a fluorescent probe for rapid and sensitive detection of cadmium ions in actual samples. The specific steps included:

[0047] (1) Preparation of fluorescent probes:

[0048] Prepare 50 mg / mL BSA and 10 mM HAuCl in double distilled water. 4 In a 50 mL round-bottom flask in a 37°C water bath, stir continuously 15 mL of HAuCl 4The solution was added to 15 mL of BSA solution. After 2 min, 1.5 mL of 1.0 M NaOH solution was added, the pH was adjusted to 12, and the mixture was stirred vigorously at 37 °C for 24 h. The color of the mixture gradually changed from light yellow to brownish yellow, and a 5 mM BSA-Au NCs solution was obtained. Further, 15 mL of 10 mM [C 16 M 2 Im]Br solution and 15mL 5mM BSA-AuNCs solution were mixed in a 50mL round-bottom flask and gently stirred for 30min at room temperature to obtain [C 16 M 2 Im]Br@BSA-Au NCs composite material was used for subsequent fluorescent probe detection of cadmium ions.

[0049] (2) Fluorescence detection of cadmium ions by probe:

[0050] 100 μL of [C 16 M 2 Im]Br@BSA-AuNCs composites and 100 μL of cadmium chloride solutions with different concentrations (10 nM, 100 nM, 400 nM, 600 nM, 800 nM, 1000 nM) were added to a centrifuge tube, and then the volume was fixed to 1.0 mL with deionized water. After shaking (25 °C, 350 r / min) for 5 min, the [C 16 M 2 Fluorescence emission spectrum of Im]Br@BSA-Au NCs composite probe; the fluorescence enhancement intensity around 620nm before and after the addition of cadmium ions was used as the ordinate and the cadmium ion concentration was used as the abscissa to obtain the standard fitting curve for fluorescence detection. The results are shown in Figure 4 In the range of 10.0-1000.0nM [C 16 M 2 The enhanced intensity (F 1 -F 0 ) and cadmium ion concentration of 1.0×10 -8 –1.0×10 -6 M range shows a linear relationship, and the linear correlation equation is fitted as F 1 -F 0 =0.3674C Cd 2+ +629.2668(R 2 =0.998). According to the 3σ / s principle (σ is the standard deviation of the blank sample, s is the slope of the linear regression curve), the sensing method is used to calculate the Cd 2+ The detection limit (LOD) was 5.09×10 -9 M.

[0051] (3) Study on the selectivity of probe for cadmium ion detection

[0052] In step (1), 100 μL [C 16 M 2 100 μL of 10 Im]Br@BSA-Au NCs composites were added separately -6 M's Cd 2+ or 100 μL 10 -4 Various heavy metal ions and other interfering ions (in the following forms: HgSO 4 、Pb(NO 3 ) 2 AgNO 3 , CuCl 2 、ZnCl 2 MgCl 2 、Al 2 (SO 4 ) 3 CrCl 3 , KCl, NiCl 2 , CaCl 2 、BaCl 2 , NaCl, MnCl 2 , oxalic acid, tartaric acid, citric acid and citric acid-heavy metal complexes), dilute to 1.0 mL with deionized water, shake (25 ° C, 350 r / min) for 5 min, and then measure the fluorescence intensity. 1 ) as the ordinate and the types of interfering ions as the abscissa, proving that the probe has excellent selectivity, such as Figure 5 As shown. Figure 5 Obviously only CD 2+ The fluorescence of the composite material was enhanced, while the fluorescence of the others was weakened. The volume of the probe solution was kept at 100 μL. 2+ (10 -6 M) were added to 100 μL of different interfering ions (10 -4 M) was added with the probe solution, and the volume was adjusted to 1.0 mL with deionized water. After shaking (25°C, 350 r / min) for 5 min, the fluorescence intensity was measured. 1 ) as the ordinate and the types of interfering ions as the abscissa to draw a bar graph, proving that the probe has a certain anti-interference ability. The results are as follows Figure 6 As shown. Figure 6 It can be seen that most ions have a strong affinity for Cd 2+ The detection of Ag + It may be obvious, and its interference can be avoided later by adding metal masking agents.

[0053] (4) Detection of cadmium ions in actual samples

[0054] Real samples including rice, seabuckthorn juice, roxburghii juice, West Lake Longjing, Pu'er tea, Wuliangye liquor, Shaoxing rice wine, apple juice, grape juice and packaged drinking water were collected. Except for the packaged drinking water, all the samples were subjected to simple pretreatment to obtain extracts. Cadmium ions (in the form of cadmium chloride) were added to the packaged drinking water and the extracts to prepare extracts containing different cadmium ion concentrations (10 -6 , 5×10 -7 , 10 -8 M) of the test solution, and the recovery rate was determined by a spiked recovery experiment. Among them: the wine sample stock solution was diluted 1000 times for subsequent experiments, and the sea buckthorn juice, sea buckthorn juice, apple juice and grape juice stock solutions were diluted 10 times for subsequent experiments. Tea leaves (0.5g) were soaked in 15.0mL of deionized water and ultrasonically treated for 30 minutes. The soaking solution was filtered through a 0.22uM filter membrane to remove insoluble impurities to obtain a tea extract, which was diluted 1000 times for subsequent experiments. The purchased rice sample was first ground into powder, and the rice powder (0.5g) was weighed and put into a beaker, and then 10mL of HNO was added. 3 (5%); soak rice flour in HNO 3 2h, ultrasonic treatment for 15min, centrifugation at 3000rpm for 10min; dilute the obtained supernatant to 25mL, and gradually add NaOH solution to adjust the pH to 7, and the obtained solution is used for subsequent experiments. -8 5.0×10 -7 , 10 -6 The fluorescence spectra of each test solution before and after the addition of cadmium ions M are calculated using the fitting curve in step (2). The results are as follows: Figure 7 As shown, the recovery rate was between 91.7-110.7% and the relative standard deviation (RSD) was less than 1.2%.

Claims

1. A method for detecting cadmium ions using an ionic liquid-modified nanogold cluster material as a fluorescent probe, characterized in that: The ionic liquid modified nanogold cluster composite material and the test sample solution are mixed. Preferably, after mixing, the reaction is carried out for 5±0.5 min and the fluorescence emission spectrum of the probe is measured. If the fluorescence intensity at 620±5 nm increases after the test sample solution is added, it is determined that the test sample solution contains cadmium ions; otherwise, the test sample solution does not contain cadmium ions.

2. The method according to claim 1, characterized in that The imidazole ionic liquid is mixed with the nano-gold clusters synthesized by taking bovine serum albumin as a stabilizer and a reducing agent to obtain the nano-gold cluster composite material modified by the ionic liquid.

3. The method according to claim 2, characterized in that The preparation method of the ionic liquid modified nano-gold cluster composite material comprises: (1) mixing HAuCl4 solution and bovine serum albumin solution, adjusting the pH range to 11-12, and vigorously stirring to synthesize a nano-gold cluster solution emitting red fluorescence; (2) mixing an imidazole ionic liquid solution and a nano-gold cluster solution, stirring, and causing electrostatic interaction between the two to obtain an ionic liquid modified nano-gold cluster composite material.

4. The method according to claim 3, characterized in that The structural formula of the imidazole ionic liquid is as follows: R is an alkyl group having 12 to 16 carbon atoms; X is Br, Cl or I.

5. The method according to claim 4, characterized in that The chemical formula of the imidazole ionic liquid is [C 16 M2Im]Br, its structural formula is as follows:

6. The method according to claim 3, characterized in that In step (2), the molar ratio of the imidazole ionic liquid to the nanogold is 2:1; preferably, the volume ratio of the imidazole ionic liquid solution to the nanogold cluster solution is 1:1; more preferably, the concentration of the imidazole ionic liquid solution is 10 mM.

7. The method according to claim 3, characterized in that In step (1), the dosage ratio of HAuCl4 and bovine serum albumin is 1 mmol:5 g; preferably, the volume ratio of HAuCl4 solution and bovine serum albumin solution is 1:1; more preferably, the concentration of HAuCl4 solution is 10 mM.

8. The method according to claim 5, characterized in that The detection limit of the ionic liquid modified gold nanocluster composite material as a fluorescent probe is 5.09×10 -9 M.

9. The method according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: S1 drawing a standard fitting curve of cadmium ions: mixing the ionic liquid modified nanogold cluster composite material and a series of cadmium ion solutions with different concentrations, fixing the volume, shaking or standing for 5 minutes, and then measuring the fluorescence emission spectrum of the probe, using the fluorescence intensity difference of 620±5nm before and after adding cadmium ions as the vertical coordinate and the cadmium ion concentration as the horizontal coordinate for linear calibration to obtain a standard fitting curve for fluorescence detection; S2 mixes the ionic liquid modified nano-gold cluster composite material and the sample solution to be tested, fixes the volume, shakes or leaves it to stand for 5 minutes, measures the fluorescence emission spectrum of the probe, and calculates the cadmium ion concentration in the sample solution to be tested using the fitting curve in S1.

10. The method according to claim 9, characterized in that The sample to be tested is food, including beverages and grains, and the raw material or dilution or extract obtained by simple pretreatment has a cadmium ion concentration of 1.0×10 -8 –1.0×10 -6 M.

Citation Information

Patent Citations

  • 2-mercaptoimidazole-bovine serum albumin-gold nanocluster fluorescent material and preparation method thereof

    CN105199717A

  • Polyacid-imidazole member containing cadmium-based fluorescent probe compound, preparation method therefor and application of polyacid-imidazole member containing cadmium-based fluorescent probe compound

    CN110016044A